Unexpected Long-Term Protection of Adult Offspring Born to High-Fat Fed Dams against Obesity Induced by a Sucrose-Rich Diet - Couvreur, Odile (Public Library of Science, 2011)
BACKGROUND: Metabolic and endocrine environment during early life is crucial for metabolic imprinting. When dams were fed a high fat diet (HF diet), rat offspring developed hypothalamic leptin resistance with lean phenotype when weaned on a normal diet. Interestingly, when grown on the HF diet, they appeared to be protected against the effects of HF diet as compared to offspring of normally fed dams. The mechanisms involved in the protective effect of maternal HF diet are unclear. METHODOLOGY/PRINCIPAL FINDINGS: We thus investigated the impact of maternal high fat diet on offspring subjected to normal or high palatable diet (P diet) on metabolic and endocrine parameters. We compared offspring born to dams fed P or HF diet. Offspring born to dams fed control or P diet, when fed P diet exhibited a higher body weight, altered hypothalamic leptin sensitivity and metabolic parameters suggesting that maternal P diet has no protective effect on offspring. Whereas, maternal HF diet reduces body weight gain and circulating triglycerides, and ameliorates corpulence index of offspring, even when subjected to P diet. Interestingly, this protective effect is differently expressed in male and female offspring. Male offspring exhibited higher energy expenditure as mirrored by increased hypothalamic UCP-2 and liver AdipoR1/R2 expression, and a profound change in the arcuate nucleus astrocytic organization. In female offspring, the most striking impact of maternal HF diet is the reduced hypothalamic expression of NPY and POMC. CONCLUSIONS/SIGNIFICANCE: HF diet given during gestation and lactation protects, at least partially, offspring from excessive weight gain through several mechanisms depending upon gender including changes in arcuate nucleus astrocytic organization and increased hypothalamic UCP-2 and liver AdipoR1/2 expression in males and reduced hypothalamic expression of NPY and POMC in females. Taken together our results reveal new mechanisms involved in the protective effect of maternal HF diet.